Ecosystem services values in Spain: A meta-analysis. Issue 55 (January 2016) - Quintas-Soriano, Cristina; Martín-López, Berta; Santos-Martín, Fernando; Loureiro, María; Montes, Carlos; Benayas, Javier; García-Llorente, Marina
Highlights: We found a dissimilar spatial distribution of the economic valuation studies in Spain. Coastal systems and forests are the most studied ecosystem types. Cultural services are the most studied but those with lower economic values. We provide evidence about the effect of methods and services on economic values. Abstract: We analyzed the state of the art in research on the economic valuation of ecosystem services in Spain. A review of 150 publications was conducted and included 649 economic value estimates. The results showed an increase in the number of scientific studies on the economic valuation of ecosystem services and a dissimilar distribution across regions. Cultural ecosystem services received the most attention, and coastal systems and forested areas were the most studied ecosystem types. We found differences in the economic value estimates among categories of services and among economic valuation methods, with provisioning services and market-based methods as those that elicited the highest economic values, respectively. Our results provide an overview of past and current economic valuation studies in Spain. In addition the results depict patterns that help in understanding the effects of different factors on economic value estimates and in providing insights for future research on ecosystem services assessment in Spain. We conclude that although economic assessments remain important in scientific and policy forums, we should also recognize additional approaches that are able to incorporate the plurality of values attached to ecosystem services.